Use of a modified disc diffusion test to detect ampc beta lactamase production in escherichia coli from cases of urinary tract infections - MAANASA BHASKAR M; JHARNA MANDAL (International Journal of Pharma and Bio Sciences, 2016)
Routine detection of AmpC beta lactamases in Escherichia coli is cumbersome. This study was performed to determine the usefulness of a modified disc diffusion test to detect AmpC beta lactamases in E.coli. 28 non-repetitive, cefoxitin resistant isolates of E.coli were collected from cases of urinary tract infections and screened phenotypically for ESBLs and AmpC beta lactamase using DDST (ceftazidime and ceftazidime-clavulanic acid for detection of ESBLs, cefoxitin-cloxacillin DDST and cefoxitin - phenylboronic acid, cefoxitin-EDTA combination discs). Genotypic detection of AmpC and ESBL genes was done by PCR along with mutation analysis of chromosomal promoter of AmpC. Of the 28 isolates, 6 strains showed enhancement of zone of inhibition in cefoxitin-cloxacillin, cefoxitin plus 400mcg of phenyl boronic acid and a combination of 400 mcg of phenyl boronic acid and 292 mcg of EDTA but not with EDTA alone. Of the 6 phenotypically AmpC beta lactamase positive strains, 4 carried plasmid AmpC beta lactamase gene.